PENGARUH FLASH SALE TERHADAP IMPULSIVE BUYING MELALUI POSITIVE EMOTION (STUDI PADA AEON STORE BSD CITY) - Hamzah , Helmy Adrian; Adryan Rachman (Publika Citra Media, 2025)
This research is motivated by the increasingly widespread phenomenon of impulsive buying in retail stores, especially Aeon Store BSD City. This phenomenon can be influenced by various things such as flash sales. Therefore, the purpose of this study is to determine the effect of flash sales on impulsive buying through positive emotions at Aeon Store BSD City. This study uses a quantitative method (ex-post facto) with data collection through the distribution of questionnaires by purposive sampling using Google Form to 176 respondents. This study uses the PLS method which is also known as